Parametric factory simulation for the responsive enterprise - Farr, Richard; Tannock, James; Holm, Sofia (2007)
Simulation offers a powerful way to investigate the boundaries of what can be achieved by a manufacturing system, demonstrating the impact of schedules and policy decisions such as the placement of buffers and the size of safety stocks. Unfortunately, the construction of factory models at the necessary level of detail is a time-consuming process, requiring specialist skills.